Centrally fed orifice based active aerostatic bearing with quasi-infinite static stiffness and high servo compliance. (January 2019) - Maamari, N.; Krebs, A.; Weikert, S.; Wegener, K.
Abstract: Active compensation of aerostatic bearing enhances their inherent limited stiffness and adds macro positioning capabilities. Current active solution relies on a position feedback to reach high stiffness. In this study, a novel concept that replaces costly position feedback by a self-regulating stiffening mechanism is investigated. This concept features a guided conical deformation based on integrated leaf springs. This balances the pressure and servo induced deformation, leading to quasi-infinite stiffness and high servo compliance. A lumped and a finite element models governing the static behavior are presented and benchmarked. Open loop stability is assessed using a linearized lumped dynamic analysis, and solutions based on a mechanical and a mechatronic approach are proposed. Finally, the prototype is tested in open loop, proving a quasi-infinite stiffness and a servo compliance of 3.4 μ m / A . Graphical abstract: Image 1 Highlights: Mechanical concept of active aerostatic bearing based on voice coil actuation ensuring a linearly varying gap geometry. Modelling using a lumped approach encapsulating thin-film, structural deformation, and magnetism. Mechanical design and finite element model compared to the lumped approach. Experimental results confirmed a quasi-infinite stiffness and a servo compliance of 3.4 μ m / A .